Praktik Manajemen Laba: Studi Komparasi pada Perusahaan-Perusahaan yang Melakukan IPO Tahun 2012-2016 - T Husain; Ade Elza Surachman (Direktorat Riset dan Pengabdian kepada Masyarakat Universitas Bina Darma, 2017)
This research was aimed to obtain empirical evidence about the practice of earnings management between companies in manufacturing industry and financial sectors listed in Indonesian Stock Exchange. This study adopted measurement of earnings management based on conditional revenue model approach. The population in this research was 41 manufacturing companies and financial sectors listed in Indonesian Stock Exchange to conduct an initial public offerings (IPO) in 2012-2016. The sampling technique was purposive method. The sample in this research establishment was 16 manufacturing industry and 22 financial sectors companies. The data analysis method using independent-samples t test, did the normality and homogenity test previously and hypothesis testing with mann-whitney test approach. The hypothesis testing results indicated that there is no significant difference between manufacturing industry and financial sectors who conduct an IPO in 2012-2016 to the practice of earnings management.